PENDIDIKAN KARAKTER SEBAGAI PONDASI PENGUATAN JATI DIRI BANGSA - Yuga Adi Kusuma (Institut Agama Islam Syarifuddin Lumajang, 2017)
The national culture and character are main issues recently. The character education in accordance with the Indonesian identity is the key in discussing the previous issues. Therefore, this type of education should be done as early as possible.